Fiscal Crisis, Economic Prospects : The Imperative for Economic Cohesion in the Palestinian Territories, Economic Monitoring Report to the Ad Hoc Liaison Committee - World Bank (World Bank, Washington, DC, 2016)
Economic growth in West Bank and Gaza (WB&G) slowed in the first quarter (Q1) of 2012. The real growth rate is estimated to have reached 5.6 percent, more than three percentage points lower than the Q1 2011 growth figure and almost one percent lower than the growth forecast contained in the Palestinian Authority's (PA's) budget. This decline is attributed to a major slowdown in Gaza, where real growth decreased from 21.3 percent to 6 percent on a year-on-year basis. The slowdown in Gaza during Q1 of 2012 was mainly attributed to a major decline in the agriculture and fishing sector, which offset much of the growth witnessed in other sectors. This sector shrank by 43 percent in Q1 2012 due to frequent power outages resulting from the lack of fuel in Gaza. Nevertheless, other sectors in Gaza expanded and the highest growth levels were witnessed in the construction, and hotels and restaurants sectors. In the West Bank, growth in Q1 2012 was broadly unchanged from its 2011 level. Most of the growth was from an expansion of services, which contributed around 2.2 percentage points of the 5.4 percent total growth in Q1 2012. The recent slowdown in economic growth is also reflected in higher unemployment levels. Overall unemployment in WB&G was 20.9 percent in the second quarter of 2012 compared to 18.7 percent during the same period in 2011. A serious concern in WB&G is the high level of youth unemployment that is accompanied by low youth participation in the labor force.